Going to School - Civardi, Anne and Cartwright, Stephen; Consultant by Root Betty (London Usborne, 1992)
Twins Percy and Polly spend their first day at school : shows very young children what to expect.
Include Color Illustrations
Keywords: Elementary Schools -- Juvenile literature